Enclisis, mesoclisis and inflection in Italo-Romance varieties: A minimalist analysis - Savoia, Leonardo M.; Baldi, Benedetta (LingBaW. Linguistics Beyond and Within, 2023)
This contribution addresses a central theme in morphological analysis, namely the relationship between clitics and inflectional elements. Important contributions on the point are due to Anderson (1992) and Marantz (1988), who, in different ways, connect clitics and affixes. We will propose a solution based on the idea that clitics are part of the inflectional arrangement of the verbal head. Specifically, we will investigate two types of data coming from some Romance varieties in which enclisis and mesoclisis phenomena interact with word formation. These phenomena affect the expression of the Internal Argument and lead us to rethink the analysis of enclisis and mesoclisis in terms of the ability of the inflected verb to realize Phasal domains. In other words, morphology is part of the syntactic computation, and morphemic elements, endowed with interpretable content, are introduced by the operation of Merge.